Investigating Social Factors Affecting Social Health Among Clients Covered by Welfare Organization in Nowshahr City, Iran - Mohammad Nabi Najafi Andarvar; Majedeh Gholipour; Abolghasem Heydarabadi; Manouchehr Pahlavan (University of Social Welfare and Rehabilitation Sciences, 2023)
Objective Social health, along with physical and mental health, is one of the pillars of health and represents one's assessment of social life. Therefore, the purpose of this study was to investigate the social factors affecting the social health of the clients covered by the Nowshahr Well-being. Materials & Methods The research method in this study was the descriptive follow-up. The research community was formed by female clients 18 to 60 years old under the cover of the Nowshahr Well-being with 3951 people. 350 samples were selected using the Morgan table and simple random sampling method. The data collection tool consisted of two valid keyes social health questionnaires (1) and Babapour et al. (2010). The reliability of the questionnaires was calculated using Cronbach's alpha method, according to which the coefficient of research variables and its dimensions were more than 0.7 and was evaluated as suitable. For research data analysis, correlation coefficient and regression analysis with SPSS software, version 24 was used. Results According to the findings of the research, there is a positive and significant relationship between all the variables, that is, between the independent variables of the research, which include social integration, social skills, social participation, and social acceptance, with the dependent variable of the research, social health. Using regression, the effect of social integration variables (β=0.137), social skills (β=0.157), social participation (β=0.156), and social acceptance (β=0.120) on social health was determined. The value of the multiple correlation coefficient of the dimensions of social integration, social skills, social participation and social acceptance with the variable of social health and its estimated value under the final regression model is equal to (0.612). The value of the coefficient of multiple determination in the final model was equal to (0.567), which indicates that 57 percent of the changes in social health can be explained by the independent variables included in the model, namely the dimensions of social integration, social skills, social participation, and social acceptance. which indicates the good fit of the model. The estimation of the coefficients of the final regression model shows that the investigated variables are all significant and each of them has different weights. Also, the regression coefficients showed that the variable of social skills (β=0.157) has the greatest impact. Conclusion According to the findings of the research, social integration, social skills, social participation, and social acceptance is an effective factors in promoting social health and feeling good and improving the quality of life and social health of clients covered by Nowshahr welfare department, so with Increasing the level of awareness and social skills of clients will also provide the basis for improving their social health.